2016
DOI: 10.1016/j.ultrasmedbio.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Displacement Signal-to-Noise Ratio for Low-Signal Radiation Force Elasticity Imaging Using Bayesian Techniques

Abstract: Radiation force-based elasticity imaging is currently being investigated as a possible diagnostic modality for a number of clinical tasks, including liver fibrosis staging and the characterization of cardiovascular tissue. In this study, we evaluate the relationship between peak displacement magnitude and image quality and propose using a Bayesian estimator to overcome the challenge of obtaining viable data in low displacement signal environments. Displacement data quality were quantified for two common radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Previous studies showed that shear wave measurements were highly reproducible for assessing breast lesions and thus observer variability is not expected to have large influence on this study 23 , 24 . Second, only patients and lesions factors were evaluated for association with shear wave propagation quality, while equipment related factors (such as thermal noise, finite signal bandwidth, and the geometric spreading and absorbing of shear waves) were no studied 25 . Third, the retrospective nature of the study could not avoid selection bias and future prospective study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that shear wave measurements were highly reproducible for assessing breast lesions and thus observer variability is not expected to have large influence on this study 23 , 24 . Second, only patients and lesions factors were evaluated for association with shear wave propagation quality, while equipment related factors (such as thermal noise, finite signal bandwidth, and the geometric spreading and absorbing of shear waves) were no studied 25 . Third, the retrospective nature of the study could not avoid selection bias and future prospective study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…There were several limitations in the study. Only patients and lesions associated factors were analyzed, while apparatus related factors, such as thermal noise, finite spatial and temporal resolution and finite signal bandwidth were not included into analysis 26 . Although the intra-operator consistency and the inter-operator consistency of QM were excellent with a Kappa value of 0.939 and 0.816 respectively, the effect of operator independence for QM still could not be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of displacement estimation technique (for example, Loupas vs. normalized cross-correlation vs. higher order techniques), the tracking kernel for estimation, and kernel for derivative estimation can also affect the final spatial resolution. Papers have been written about each of these individual aspects and the authors refer the readers to the literature in these cases (Pinton 2006; Byram 2013; Dumont 2016). The Savitzky-Golay filter used in this paper is based on least squares polynomial regression with the derivative being calculated based on the polynomial fit.…”
Section: Discussionmentioning
confidence: 99%